2022
DOI: 10.1021/acssensors.2c00300
|View full text |Cite
|
Sign up to set email alerts
|

Dip-and-Read, Organic Solvent-Compatible, Paper-Based Analytical Devices Equipped with Chromatographic Separation for Indole Analysis in Shrimp

Abstract: We developed an organic solvent-compatible paper-based analytical device (PAD) for the quantitative analysis of indole, which is an indicator of shrimp freshness. Although indole is insoluble in water, ethyl acetate is a suitable solvent to dissolve and extract indole from shrimp. The PADs are fabricated using a cutting method that allows the use of an organic solvent because no hydrophobic barrier is needed to form fluidic channels. Ehrlich’s reagent consists of 4-(dimethylamino)­benzaldehyde and p-dimethylam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The transformation of hydroxylamine 2 to O -acylalkoxyamine 3 could prevent reoxidation and provide better precision. In recent years, colorimetric paper strips or paper-based sensors have been extensively investigated as devices to quantify various analytes, such as heavy metals, 21 carcinogenic organic compounds present in food products, 22 carcinoembryonic antigens (a tumor marker), 23 dopamine, 24 cysteine 25 and other biologically relevant analytes 26 since they are easily handled. However, to the best of our knowledge, the quantitative analysis of AA on a paper-based sensor using profluorescent nitroxide probes has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…The transformation of hydroxylamine 2 to O -acylalkoxyamine 3 could prevent reoxidation and provide better precision. In recent years, colorimetric paper strips or paper-based sensors have been extensively investigated as devices to quantify various analytes, such as heavy metals, 21 carcinogenic organic compounds present in food products, 22 carcinoembryonic antigens (a tumor marker), 23 dopamine, 24 cysteine 25 and other biologically relevant analytes 26 since they are easily handled. However, to the best of our knowledge, the quantitative analysis of AA on a paper-based sensor using profluorescent nitroxide probes has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…putrefaciens, respectively. Indole is a tryptophan-derived substance that appears in protein structure and can be broken down and metabolized by the tryptophanase enzyme found in some mesophilic bacteria . Color response of indicator arrays exposed at 10 3 CFU/mL of S.…”
Section: Resultsmentioning
confidence: 99%
“…The indole is a signal molecule to evaluate freshness of shrimp . The US Food and Drug Administration (FDA) categorized fresh shrimp as primary freshness within an indole concentration of no more than 25 μg/100 g, whereas indole concentration ≥25 μg/100 g was considered as secondary freshness and spoiled shrimp .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have demonstrated applications of the PADs to different types of food and environmental samples using detection schemes such as colorimetry, electrochemistry, fluorometry, and chemiluminescence. Colorimetry is the most frequently employed detection method because it is simple to achieve qualitative and quantitative analyses of analytes by observing the color change in the detection zones on the PAD. The color images are captured with a digital camera, smartphone, or scanner, which then is followed by image processing using software such as ImageJ. , …”
Section: Introductionmentioning
confidence: 99%